Interaction between Transform Faults and Rift Systems: A Combined Field and Experimental Approach - Tibaldi, Alessandro; Bonali, Fabio L.; Pasquaré Mariotto, Federico A. (Frontiers in Earth Science, 2016)
We present a detailed field structural survey of the area of interaction between the active NW-striking transform Husavik-Flatey Fault (HFF) and the N-S Theystareykir Fissure Swarm (TFS), in North Iceland, integrated by analogue scaled models. Field data contribute to a better understanding of how transform faults work, at a much higher detail than classical marine geophysical studies. Analogue experiments are conducted to analyse the fracture patterns resulting from different possible cases where transform faulting accompanies or postpones the rift motions; different tectonic block configurations are also considered. West of the intersection between the transform fault (HFF) and the rift zone (TFS), the former splays with a gradual bending giving rise to a leading extensional imbricate fan. The westernmost structure of the rift, the N-S Gudfinnugja Fault (GF), is divided into two segments: the southern segment makes a junction with the HFF and is part of the imbricate fan; north of the junction instead, the northern GF appears right-laterally offset by about 20 m. Southeast of the junction, along the possible prolongation of the HFF across the TFS, the strike of the rift faults rotates in an anticlockwise direction, attaining a NNW-SSE orientation. Moreover, the TFS faults north of the HFF prolongation are fewer and have smaller offsets than those located to the south. Through the comparison between the structural data collected in the field at the HFF-TFS connection zone and a set of scaled experiments, we confirm a prolongation of the HFF through the rift, although here the transform fault has a much lower slip-rate than west of the junction. Our data suggest that transform fault terminations may be more complex than previously known, and propagate across a rift through a modification of the rift pattern.